Dune deformation in a multi‐directional wind regime: White Sands Dune Field, New Mexico. Issue 7 (28th January 2015) - Pedersen, Anine; Kocurek, Gary; Mohrig, David; Smith, Virginia
Abstract As with most dune fields, the White Sands Dune Field in New Mexico forms in a wind regime that is not unimodal. In this study, crescentic dune shape change (deformation) with migration at White Sands was explored in a time series of five LiDAR‐derived digital elevation models (DEMs) and compared to a record of wind direction and speed during the same period. For the study period of June 2007 to June 2010, 244 sand‐transporting wind events occurred and define a dominant wind mode from the SW and lesser modes from the NNW and SSE. Based upon difference maps and tracing of dune brinklines, overall dune behavior consists of crest‐normal migration to the NE, but also along‐crest migration of dune sinuosity and stoss superimposed dunes to the SE. The SW winds are transverse to dune orientations and cause most forward migration. The NNW winds cause along‐crest migration of dune sinuosity and stoss bedforms, as well as SE migration of NE‐trending dune terminations. The SSE winds cause ephemeral dune deformation, especially crestal slipface reversals. The dunes deform with migration because of differences in dune‐segment size, and differences in the lee‐face deposition rate as a function of the incidence angle between the wind direction and the local brinkline orientation. Each wind event deforms dune shape, this new shape then serves as the boundary condition for the next wind event. Shared incidence‐angle control on dune deformation and lee‐face stratification types allows for an idealized model for White Sands dunes. Copyright © 2015 John Wiley & Sons, Ltd.